PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN AKUNTANSI PAJAK PERTAMBAHAN NILAI PT. VP INTERNATIONAL LOGISTICS INDONESIA - Hidayat, Achmad; Hidayat, Naufal; Pranita, Fera Lufhidarani (JURNAL LENTERA AKUNTANSI, 2025)
Calculation, payment, reporting, and recording of Value Added Tax (VAT) at PT. VP International Logistics Indonesia. VAT is an indirect tax on the consumption of Taxable Goods and/or Taxable Services within the customs area, as regulated in Law Number 8 of 1983, most recently amended by Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP). The method used was descriptive qualitative, with data collection techniques including observation, interviews, and documentation studies conducted during the March 2025 tax period. The results of the study indicate that the company has fulfilled its tax obligations in accordance with applicable regulations. This process includes issuing tax invoices with the appropriate object code, calculating VAT based on the replacement value or effective rate, making payments through the Billing System menu integrated with e-Billing, reporting Periodic Tax Returns through the Coretax application, and maintaining accounting records according to standards. This implementation reflects compliance with the self-assessment system adopted in the Indonesian taxation system and complies with the provisions of PER-14/PJ/2022 and PMK No. 58/PMK.03/2022. Therefore, the company has implemented tax administration in an orderly and accountable manner.